Methods of forming health-preserving competence of participants of social and psychological rehabilitation programs - Vasiuta, Olena (Global Prosperity, 2022)
This article is considered the methods of formation of health-preserving competence as the basis of modern programs of social and psychological rehabilitation of women injured as a result of hostilities on the territory of Ukraine. War in Ukraine is going on, and this creates new challenges for all systems of society’s functioning: from the functioning of the socio-economic sector to the activities of specialists in the sphere of socio-psychological work, assistance, rehabilitation, and social security. Such prolonged stress has a negative effect not only on the person’s psychological and emotional state but also on his own psychological "I"-construction: a person begins to identify himself with the whole nation and experience powerful pain, sympathizing with many others, accepting other people’s suffering as his own, but also at the same time, forbids herself to show positive emotions, rest and distract herself from information processes. Often, the deterioration of the psycho-emotional state of such a person also contributes to the lack of skills to restore spiritual resources and physical strength. The rehabilitation program "I-course" based on the main principles of the health-preserving competence’s formation contains: a toolkit of teaching methods of harmonizing all components of human health (physical, psychological and social), providing social and psychological support, correction of the existing human condition, and reveals a multifaceted world therapy. Using such programs when working with a victim as a result of hostilities on the territory of Ukraine will provide its participants with the opportunity to independently monitor and maintain their psycho-emotional state in the future and develop an algorithm of action in case the situation worsens.